Therapeutic efficacy of a combined sage and bitter apple phytopharmaceutical in chronic DSS-induced colitis. Issue 1 (December 2017) - Hoffmann, Maximilian; Schwertassek, Ulla; Seydel, Aleksandra; Weber, Klaus; Hauschildt, Sunna; Lehmann, Jörg
Abstract Inflammatory bowel diseases are multifactorial disorders of the gastrointestinal tract with rising incidence worldwide. Current standard therapies are only partially effective and often show severe adverse effects. Thus, novel, more efficient and well-tolerated therapeutic options are urgently needed. We have studied the therapeutic potential of a phytopharmaceutical combining sage and bitter apple (SBA) in the mouse model of chronic dextran sulfate sodium (DSS) colitis. SBA represents a traditional medicine against diarrhea and was shown to exhibit anti-inflammatory effectsin vitro . In the chronic DSS colitis model SBA treatment significantly reduced clinical symptoms in a dose-dependent manner. The positive therapeutic effect of SBA was characterized by a decreased histopathological score indicating tissue healing. Moreover, the number of neutrophils as well as the expression of the neutrophil-recruiting chemokine CXCL-1/KC in the colon tissue was significantly reduced, whereas the recruitment of macrophages was induced. Also, the expression of inflammatory markers was significantly suppressed, while the expression of the anti-inflammatory cytokine interleukin-10 was induced in colon tissue following treatment with SBA. Phytopharmaceuticals are increasingly recognized as potential therapeutics in IBD. Thus, based on the results from this study, SBA can be considered as an alternative or supplementary option for IBD therapy.